PENGARUH REALISASI PENERIMAAN PAJAK BAGI PERTUMBUHAN PEREKONOMIAN NEGARA INDONESIA - Wahyu Nuning Sumaryani (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
Economic growth is a matter of the economy in the long term and is influenced by various factors. This study aimed to analyze the effects of taxes, inflation, unemployment, and education to economic growth in Indonesia. The analytical method used is the Error Correction Model (ECM). For the purpose of analysis used secondary data such as time series, 1988 - 2017, ie tax revenue, inflation, unemployment and education of Indonesia's GDP. Data were obtained from the Central Statistics Agency (BPS). The estimated using Error Correction Model (ECM) in examining the factors that influence the growth of the economy showed that the short-term and long-term tax revenue have a positive effect, in the long term inflation is positive and significant. Unemployment in the long-term positive and significant impact, while education is also a positive influence and significant impact on economic growth in Indonesia. Indonesia's economic growth will be enhanced by a variety of ways, including the government should to maximize tax revenue as a source of national development costs, control and curb inflation, increase employment and labor-intensive orientation, and improve the quality of human resources as economic actors and to improve the quality of education.